Development of Arabic Language Teaching Material in Modern Textbooks Based on the Muhammadiyah Middle School Curriculum: تطوير مادة تعليم اللغة العربية فى كتاب العصرى على أساس منهج مدرسة محمدية المتوسطة (بالتطبيق لطلاب الصف السابع بمدرسة محمدية السابع عشرة المتوسطة سورابايا) - Silvia Virda Susanti (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2021)
Good teaching book is that observing the necessity, problems and mistakes of students and teacher in teaching for solving the languange mistakes. The research purpose is to know the developing, practicing and effectivity the Arabic language teaching book from Al-Ashry based on Ismuba 2017 curriculum for students of seventh grade of seventen Muhammadiyah junior high School. The researcher used the quantitative, Research and developing method, as for the method to collect the data is using interview, questionnaire, observation, trial, pretest and posttest. The researcher used t test to know the effectively of Arabic language teaching book from Al-Ashry based on Ismuba 2017 curriculum for students of seventh grade of seventen Muhammadiyah junior high School, and she got from pretest and posttest that the result from t stat -24,9 and t critical two tail 2,014. If the t stat is smaller than t critical two tail, then the Arabic language teaching book from Al-Ashry based on Ismuba 2017 curriculum for students of seventh grade of seventen Muhammadiyah junior high School is effective. Students understanding abuot Arabic lesson increased after using this developing of teaching book.